Analysis of Flood Vulnerability Level at Secondary Schools in Ranah Pesisir Sub-District - Wijayanto, Bayu; Cynthia, Fiona; Astuti, Juli; Femilia, Vanessa Nara; Rahman, Bima; Handayani, Alifvia Putri; Addawiyah, Jamiatul; Nofrion, Nofrion; Malusu, Daudi Richard; Gharamah, Fadhl Mohammed Awadh (Pusat Kajian Berkelanjutan UIN Sulthan Thaha Saifuddin Jambi, 2025)
Ranah Pesisir Subdistrict, located in Pesisir Selatan Regency, is a flood-prone area due to its lowland geographical condition and proximity to the coastline and rivers. This study aims to analyze the flood vulnerability levels of secondary schools using a quantitative descriptive approach based on Geographic Information System (GIS). The study also seeks to describe the preparedness level of schools in mitigating flood disasters in Ranah Pesisir Subdistrict. Parameters analyzed include elevation, slope, rainfall, soil type, land use, and river proximity.The results show that the majority of secondary schools analyzed are located in zones categorized as